Perkembangan ilmu pengetahuan dalam perspektif filsafat: dari yunani kuno hingga abad pertengahan - Afrianti, Mike (Maliki Interdisciplinary Journal, 2025)
The development of science refers to a journey that is influenced by ideas in each period. influenced by philosophical ideas in each period. From a philosophical point of view, the knowledge gained during the life of the Ancient Greeks is characterized by an attempt to understand the world in a systematic and unique way. is characterized by an attempt to understand the world in a systematic and unique way. as Thales, Pythagoras, and Aristotle emphasized the need to apply the principles of epistemology, logic, and metaphysics. this was followed by interactions with Hellenistic and Roman traditions. Science entered the Middle Ages with a new nuance with the integration of religious views. influenced by theology, particularly in Christian, Islamic, and Jewish contexts. Philosophers such as Thomas Aquinas and Al-Farabi developed a symbiotic relationship between Greek philosophy and religious doctrine, thereby establishing a logical approach to philosophical belief and religious doctrine, thereby establishing a logical approach to spiritual belief. This article examines the development of science from Ancient Greece to the Middle Ages from a philosophical perspective.